Gaya Bahasa Ddalam Lirik Lagu Shalawat Nissa Sabyan dan Implikasinya Terhadap Studi Stilistika (Ilmu Uslub) - Akhad Syahid; Ika Selviana (Al-Fathin: Jurnal Bahasa dan Sastra Arab, 2018)
The Dimension of Cretivity is a condition, or condition that is particularly characteristic and almost impossible to formulate completely, which the meaning is never fully understood, because each child has a level of creativity. Creativity involves the synthesis of all these functions. The section presented here is an integrative model that includes four basic functions: (a) national thinking, (b) emotional development or high-level feelings, (c) development of special talents in the mental and physical life, and (d) the high degree of consciousness resulting in the use of imagination, fantasy, and break-through at the state of consciousness or unconsciousness. The semantics mean the theory of meaning or theory of meaning. Various kinds of complicated problems such as hostility, anger, resentment, humiliation, killing and even war in the world community generally and the people of Indonesia in particular occurs due to mistakes in saying words and sentences that berdampat on the meaning of words and sentences are diverse to cause conflict between hostility and hatred among ethnic communities and religion. It is a phrase Arabic proverb which means "The word can penetrate something that can not be penetrated by a needle", and also the expression "The survival of a person lies in how he keeps his mouth and his words".